Особливості стану слизової оболонки порожнини рота і тканин пародонта в дітей-інвалідів із порушеннями психіки - Гавриленко, Марина Аркадіївна; Gavrilenko, M. A. (My University, 2015)
Аналізуючи дані сучасної літератури [1, 2, 3, 4], можна зробити висновок про те, що надання стоматологічної допомоги дітям із психічними розладами потребує особливої уваги. Показники поширеності розладів психіки та поведінки в Україні поступово зростають. У 2009 році під наглядом дитячих психіатрів перебували 220 890 дітей у віці 0-14 років. На дитячий вік припадає 8,8% інвалідності, зумовленої розладами психіки. У 2009 році в Україні налічувалося 23 979 дітей-інвалідів із розладами психіки, первинна інвалідність була встановлена у 2352 дітей [4]. На практиці ми стикаємося з проблемою неможливості виконання чинних протоколів стоматологічного лікування, а також проведення профілактичних процедур таким дітям [3]. Це пов’язано зі специфічною поведінкою дітей із психічними розладами, тому виникає небезпека для здоров’я дитини і лікаря при використанні бормашини, стоматологічних інструментів. У цій групі пацієнтів необхідно оптимізувати розробку сучасних методів профілактики, вдосконалити підхід надання стоматологічної допомоги. 98 disabled children with mental disorders in children aged 2 to 18 years living in Zaporizhzhya and Zaporizhzhya region were observed. High prevalence and intensity of diseases of parodontium tissues. Analyzing the data of contemporary literature it can be concluded that the provision of dental care to children with mental disorders requires special attention. In practice, we face to the problem of impossibility to perform the existing protocols of dental treatment as well as implementation of preventive procedures for such children. It is connected with the specific behavior of children with mental disorders. In this group of such patients it is necessary to optimize the development of modern methods of prevention and to improve the dental care approach. Aim of the research: to study the features of the condition of periodontal tissues and mucous membrane in children with mental disorders: to examine the condition of oral hygiene; to evaluate the status of periodontal tissues; to study the features of dentoalveolar anomalies. Materials and methods. 98 disabled children with mental disorders aged from 2 to 18 years were examined. Diagnosis of the underlying disease was established by child psychiatrist. Children were divided into the age categories accordingly to the periods of teeth development: temporary bite – 2-5 years old (group I, 39 children), changeable bite – 6-10 years old (group II, 31 children), permanent bite – 11-18 years old (group III, 28 children). Oral hygiene was evaluated according to Yu.A. Fedorov and V.V. Volodkina, Green and Vermillion. Processing of quantitative indices was carried out using Student's t-test (Р ≤ 0,01). Condition of periodontal tissues were evaluated on the basis of determination of papillary-marginal-alveolar index (PMA) in the modification of Parma (1960) and communal periodontal index CPI (1998) recommended by the WHO. Features of dentoalveolar disorders were evaluated by visual dental inspection because imprints of teeth cannot be made due to the underlying disease.
Features of condition of periodontal tissues in disabled children with mental disorders
Keywords: disabled children with mental disorders; gingivitis; periodontitis